RISK FACTORS OF PULMONARY TUBERCULOSIS IN CHILDREN (0-14 YEARS): SYSTEMATIC LITERATURE REVIEW (Proceedings of the International Conference on Public Health, 2025)
Pulmonary tuberculosis poses a major global health challenge, particularly among children. Accurate and early diagnosis is critical for effective treatment, yet diagnosing pulmonary tuberculosis in children is often complicated by their nonspecific clinical symptoms and the difficulties in collecting samples. This study aims to identify the risk factors and comorbidities associated with tuberculosis in children. The research methodology employed is a systematic literature review (SLR), with data gathered by documenting all relevant international journal articles sourced from four databases such as Google Scholar, PubMed, Scopus, and ProQuest. During the review process using the PRISMA Flow Diagram, only 7 of the 152 records were initially identified after applying inclusion and exclusion criteria. Key results reveal that HIV infection greatly increases the risk of tuberculosis in children due to weakened immune systems. Malnutrition is another significant factor, with undernourished children facing a much higher risk of contracting tuberculosis. Breastfeeding practices were also found to influence tuberculosis rates, with improper practices associated with higher incidences. Additionally, a history of contact with tuberculosis patients and lower socioeconomic status were found to increase the likelihood of developing the disease. Vitamin D deficiency was also identified as a potential factor influencing tuberculosis outcomes in children. This study highlights several key risk factors for pediatric pulmonary tuberculosis. Tackling these issues through comprehensive healthcare measures could improve early detection and targeted interventions, so it has better health outcomes for children at risk. The government's policy strategy regarding End TB 2030 is also the basis for what must be done immediately to prevent an increase in pulmonary tuberculosis mortality rates.
Keywords: children; HIV; malnutrition; pulmonary tuberculosis; risk factors; systematic literature review